2007
DOI: 10.1093/nar/gkl735
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease activity of the MutS homologue MutS2 from Thermus thermophilus is confined to the Smr domain

Abstract: MutS homologues are highly conserved enzymes engaged in DNA mismatch repair (MMR), meiotic recombination and other DNA modifications. Genome sequencing projects have revealed that bacteria and plants possess a MutS homologue, MutS2. MutS2 lacks the mismatch-recognition domain of MutS, but contains an extra C-terminal region called the small MutS-related (Smr) domain. Sequences homologous to the Smr domain are annotated as ‘proteins of unknown function’ in various organisms ranging from bacteria to human. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 33 publications
6
71
1
Order By: Relevance
“…On the other hand, an expression of the N60-ttmutS2 mutant did not give rise to a serious decrease in the survival ratio. We have reported that the N60-ttMutS2 mutant binds to dsDNA as tightly as wild-type ttMutS2, however, N60-ttMutS2 does not retain the endonuclease activity (17). The endonuclease activity of ttMutS2 would be required for complete suppression of homologous recombination.…”
Section: Crystal Structure Of the Ttmuts2mentioning
confidence: 95%
See 4 more Smart Citations
“…On the other hand, an expression of the N60-ttmutS2 mutant did not give rise to a serious decrease in the survival ratio. We have reported that the N60-ttMutS2 mutant binds to dsDNA as tightly as wild-type ttMutS2, however, N60-ttMutS2 does not retain the endonuclease activity (17). The endonuclease activity of ttMutS2 would be required for complete suppression of homologous recombination.…”
Section: Crystal Structure Of the Ttmuts2mentioning
confidence: 95%
“…Plasmids pET-11a/ttmutS2, pET-11a/N60-ttmutS2, and pET-15b/ttSmr 621 , derived from pET-11a and pET-15b (Novagen), contain the complete, 3Ј-terminal region-deleted, and 5Ј-terminal region-deleted ttmutS2 genes, respectively, under control of a T7 promoter (17). ttMutS2, N60-ttMutS2, ttSmr 621 , and T. thermophilus MutS1 (ttMutS1) were overexpressed and purified as described previously (17,22). A DNA fragment expressing the ttSmr 663 domain was generated by PCR using the T. thermophilus HB8 genomic DNA as a template.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations